2022
DOI: 10.1007/s10055-022-00636-4
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on cybersickness: pervasiveness, latent trajectories, susceptibility, and effects on the virtual reality experience

Abstract: Although virtual reality (VR) usage has become widespread in the last decade, its adoption has been hampered by experiences of user discomfort known as cybersickness. The present study, in line with the “2020 cybersickness R&D agenda”, sought to provide a broad examination of the cybersickness phenomenon, assessing its pervasiveness, latent trajectories, impacts on the VR experience, and predictor variables. The study was composed of 92 participants living in the Dominican Republic with ages ranging from 18 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 100 publications
0
18
1
Order By: Relevance
“…At the same time, since VR sickness is a negative embodied experience (i.e., felt "in the body"), feeling of physical discomfort is a likely outcome for people who are experiencing VR sickness. Similarly, research shows that VR sickness also negatively influences the intention to adopt and use VR technology (Garrido et al 2022;Sagnier et al 2020).…”
Section: Inconvenience-related Hypothesesmentioning
confidence: 98%
“…At the same time, since VR sickness is a negative embodied experience (i.e., felt "in the body"), feeling of physical discomfort is a likely outcome for people who are experiencing VR sickness. Similarly, research shows that VR sickness also negatively influences the intention to adopt and use VR technology (Garrido et al 2022;Sagnier et al 2020).…”
Section: Inconvenience-related Hypothesesmentioning
confidence: 98%
“…As there was no correlation between individual susceptibility to CS, as measured by the MSSQ-short questionnaire [11,26], and response to the stimulation, it can be postulated that tACS may be worth trying in all subjects experiencing nausea when undergoing to VR immersion. That the subjective questionnaire was not predictive of the subsequent response to 10 Hz-tACS may be due to the fact that the MSSQ is not specific for susceptibility CS but rather to kinetosis in general [35]. The fact that 2 Hz-tACS did not significantly worsen subjective nausea as did in normal subjects during posturographic testing [36] (although nausea increased in 44% of subjects) may be explained by the fact that the level of nausea during the ride was already quite high, making it difficult to be further significantly worsened by the stimulation.…”
Section: Discussionmentioning
confidence: 92%
“…This is similar to previous studies investigating the use of VR where more than half of participants reported symptoms of cybersickness with fully immersive VR. 20,21 In a fully immersive VR environment, the vection perception is generally enhanced. Although it was not fully understood why some individuals and not others experienced cybersickness, the sensory conflict between vestibular, visual, and somatosensory input could be a likely cause based on the sensory conflict theory.…”
Section: Discussionmentioning
confidence: 99%